The Non-contagious Pityriasis versicolor in an Adult male treated with Individualized Homoeopathic Intervention: A descriptive study (Case Report) - Das, Abhinandan (Indian Journal of Integrative Medicine, 2023)
Tinea versicolor, also known as Pityriasis versicolor, is a common, non-painful, non-contagious, benign, superficial fungal infection of the skin. Pityriasis versicolor is caused by Malassezia globose or few times Malassezia furfur, a dimorphic lipophilic fungus, also known as Pityrosporum. Meanwhile, they live in our body as a symbiotic relationship. P.V distribution of affected skin reflects the lipophilic nature of the fungus since the seborrheic areas (trunk, neck, and/or arms) are predominantly involved. P.V. not properly cured in conservative treatment, they must use palliative mode of treatment, whereas in homoeopathy lots of probabilities to cure are lurking up. Homoeopathy is a part of traditional complementary alternative medicine & it’s very low cost, easily available, no side effects nor the palliative mode of treatment, that’s why maybe it’s the prime choice for P.V. mana-gement. We are presenting a P.V. case successfully treated by individualized homeopathic medicine without local application.